Outcome of total thyroidectomy and subtotal thyroidectomy in non-toxic multinodular goiter: Hospital Universiti Sains Malaysia Experience - Mohamad, Ikhwan Sani; Mohamad, Irfan; Baw, Shwe; Kamarulzaman, Mohd Nazli; S, Hassan; Rahman, Mohd Nor Gohar (University Putra Malaysia, 2013)
Introduction: Thyroid enlargement is one of the common surgical presentations in the Department of Surgery, Hospital Universiti Sains Malaysia (HUSM). Among them, benign non-toxic multinodular goiter constitutes one third (30%) of patients who underwent thyroidectomy. Common complications of thyroidectomy include recurrent laryngeal nerve (RLN) injury, hypocalcaemia, and recurrence of the thyroid lesion. Objective & Methods: This is a retrospective study of patients diagnosed with multinodular goiter treated in HUSM between January 1996 and December 2005. A total of 111 patients were studied and 52 of them underwent subtotal thyroidectomy while 59 underwent total thyroidectomy. The outcome in terms of RLN injury, hypocalcaemia and mass recurrence were analyzed. Results: Post operative complications were studied in both groups. Permanent recurrent laryngeal nerve injury occurs in 2.4% (1 case) in subtotal thyroidectomy group compared to total thyroidectomy group (3.6%, 2 cases). Five cases from total thyroidectomy group suffered from permanent hypocalcaemia but none in the other group. 70.7% (29 cases) from subtotal thyroidectomy group have functional remnant of thyroid tissue. Recurrence rate post subtotal thyroidectomy after 5 years is only 4.9% (2 cases). Conclusion: The post operative outcome in patients who underwent subtotal thyroidectomy in HUSM from January 1996 to December 2005 was better than total thyroidectomy with significant functional thyroid remnant.